Menanamkan Jiwa Kreativitas dan Kewirausahaan Santri Melalui Lomba Islami di Majlis Ta’lim Miftahul Khoirot Desa Cibinong Jatiluhur Purwakarta - Sodik, Muhammad; Saepudin, Ahmad; Suryadi, Yadi (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Creativity is needed for every individual, including children or students, in order to face challenges and intense competition in the growing era of globalization. Each individual is challenged to be able to create unique works or ideas, as well as something different from the existing ones to be able to win the competition. Santri are not only equipped with ukhrawi affairs, but it is also important to be equipped with worldly knowledge, as one of the provisions to maintain survival and social life. Creativity must always be trained in order to continue to grow. This PKM program aims to motivate students to be more active in studying Islam, generate and develop students' hidden talents by honing creativity in accordance with the categories of interest, as well as providing an understanding of creativity and entrepreneurship. This PKM method uses counseling, and practice. The results of this PKM can be concluded that the Community Service program at Majlis Ta'lim Miftahul Khoirot has been carried out well and the goals set have been achieved. This PKM activity is only at the stage of making students more confident in expressing themselves, increasing creativity, and fostering an entrepreneurial spirit. To start entrepreneurship, serious efforts are needed, of course, from the Majlis Ta'lim Miftahul Khoirot to support and provide more assistance in an effort to help the children of students at the Majlis Ta'lim Miftahul Khoirot to start entrepreneurship